Genotyping of news variants of the avian infectious bronchitis virus from Tolima department, Colombia - Cifuentes-Rincon, Analorena [UNESP]; Lopes, Priscila D. [UNESP]; Sanmiguel P, Rosa A. (Univ Cordoba, 2016)
Objective. The aim of this study was identify the different genotypes of infectious bronchitis virus (IVB) present in commercial poultry farms from different localities of the Tolima Department, Colombia. Materials and methods. 105 samples of tracheal swabs of poultry of 21 farms were collected. Poultry had been vaccinated against IVB. An screen to identify positive samples and posteriorly the sequencing of the partial region of the S1 subunit and phylogenetic analysis of the isolates with the reference strains, including the vaccine currently used in the country was performed. Results. Poultry all farms had respiratory signs, but only four farms was confirmed the disease. Positive samples of the IBV (HT6, HT9, HT10 and HT11) were pathogenic for embryos 9-days-old. The HT6 sample was grouped in the same cluster that the Massachusetts strains. The HT9 and HT11 samples showed 99% similarity and were grouped genetically distant from the reference strains and other isolated. The HT10 sample showed low similarities with the isolates and reference strains, grouping alone in another cluster. Conclusions. New genotypes are circulating in the Tolima Department, where there is a risk of genetic recombination. Is believed that vaccines used were not providing cross-protection against the new genotypes.
Keywords: Characterization; S1 gene; isolation; purification (Source: DeCS)